Cystic epithelioid malignant mesothelioma of the mesentery with rapid postoperative metastasis: an unusual case report - Ting Xu; Xue Meng; Xuan Gou; Xinyuan Wang; Shuai Luo; Deyuan Zhang (Frontiers in Medicine, 2026)
Background Epithelioid malignant mesothelioma is a subtype of peritoneal mesothelioma associated with a relatively better prognosis. Herein, we report a case of epithelioid malignant mesothelioma in a 50-year-old Chinese female without a history of asbestos exposure. The tumor initially presented as a localized cystic mesenteric lesion. However, metastasis to the liver margin was detected 22 days after surgery, accompanied by rapid disease progression within one month. Gross examination revealed a cystic mass. Histologically, the tumor was consistent with epithelioid malignant mesothelioma, a rare pathological finding. Case demonstration A 50-year-old female patient was admitted with a two-month history of right lower quadrant abdominal pain and no reported asbestos exposure. Ultrasound revealed a cystic structure of undetermined nature and origin in the right lower abdomen. Contrast-enhanced magnetic resonance imaging (MRI) of the mid-to-lower abdomen demonstrated a round mass adjacent to the cecum, measuring 47 × 40 × 59 mm. On T1-weighted imaging, the lesion exhibited high signal intensity on in-phase, out-of-phase, and fat-suppressed sequences; on T2-weighted imaging, it appeared isointense to slightly hyperintense. The mass wall was unevenly thickened with irregular margins. The central area of the lesion showed no enhancement and appeared hypointense. The mass was located in the pericecal region, suggesting a cystic mesenchymal tumor. Postoperative pathological examination confirmed the diagnosis of localized epithelioid malignant mesothelioma of the mesentery. Metastasis was detected 22 days after surgery. Conclusions We report this rare case of localized malignant mesothelioma to raise awareness among clinical pathologists of this entity, facilitate accurate diagnosis, and help avoid misdiagnosis.